Literature Review Skema Proteksi Jaringan Distribusi Yang Terhubung Dengan Pembangkit Tersebar - Yamashika, Herris; Syafii, Syafii; Adrianti, Adrianti; Aulia, Aulia (Majalah Ilmiah Teknologi Elektro, 2023)
Connecting distributed generation (DG) to the distribution network faces several challenges. One of them is related to the protection sistem scheme. The coordination of the existing protection sistem is unable to work properly with DG connected. Changes in short circuit current level, bidirectional power flow, blinding protection, false trip, and auto recloser failure are the problems presented in this paper. Several researchers have developed a protection scheme to overcome this problem. This article reviews some schemes that have been proposed previously. The article to be reviewed is only for AC sistems and does not include signal processing methods due to the complexity of the implementation stage. The protection scheme under review consists of adaptive scheme, differential scheme, distance relay scheme, voltage scheme, fault current limiter (FCL) scheme, and overcurrent protection scheme. The results of the review show that the proposed scheme has not considered DG with an inverter interface. The use of expensive communication channels is still a mainstay in adaptive and differential schemes. Transient problems due to DG connection and disconnection, as well as unbalanced loading, are also encountered. Keyword— distributed generation protection; AC microgrid; Distributed Generation/DG